Evolução dos perfis elétricos e mecânicos da motilidade colônica em modelo animal de doença inflamatória intestinal - Calabresi, Marcos Felipe de Freitas [UNESP] (2017)
Inflammatory bowel disease (IBD) is an idiopathic gastrintestinal tract disease that affects a large part of the world population and has its symptoms related to changes in colon motility. However, the evolution of these changes is not completely understood, and may be related to symptoms that appear in stages when the disease is apparently controlled. The objective of this work was to perform a long-term evaluation of the mechanical and electrical aspects of colonic contractility during the model of inflammation induced by trinitrobenzene sulfonic acid (TNBS) in rats. This work applied an efficient and low invasive methodology associating mechanical, electrical, chemical and histological information. The contractility and inflammatory parameters were acquired in the same animal at six different times: before induction of TNBS (control) and at 2, 5, 8, 11 and 14 days thereafter. The mechanical activities were acquired by Alternating Current Biosusceptometry (ACB) and subdivided in Rhythmic Propagation Ripples (RPR) and Rhythmic Propulsive Motor Complex (RPMC). We recorded the electrical activity by electromyography (EMG) and evaluated the inflammation processes determining the myeloperoxidase activity (MPO) in the feces. Additionally, we compared the thickness of colon layers throughout the inflammation by histopathological analyzes. Our results showed transient changes in MPO activity levels and frequency of RPMC contraction, while RPR and electrical activity underwent permanent changes. In addition, the association of these results with tissue layer thickness revealed the possible influence of fibrosis and depth of lesion on the different types of Cajal Interstitial Cells (ICCs). The general analysis of the results showed a clear relationship between the different profiles of the contractile alterations, degrees of intestinal inflammation, tissue damage morphology and classic IBD symptoms. The approach developed here opens new horizons for new work exploring the interdependence between different types of inflammatory model, drug application and its motor consequences.